2018
DOI: 10.1542/peds.2017-2741
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrest Survival in Pediatric and General Emergency Departments

Abstract: In a nationally representative sample, survival from nontraumatic OHCA was higher in pediatric EDs than general EDs. Survival did not differ in traumatic OHCA. Identifying the features of pediatric ED OHCA care leading to higher survival could be translated into improved survival for children nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 28 publications
2
61
3
Order By: Relevance
“…However, higher adherence was noted for the BLS domain. This finding contrasts with recent clinical data demonstrating improved survival in children presenting to higher‐pediatric‐volume EDs and academic medical centers …”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…However, higher adherence was noted for the BLS domain. This finding contrasts with recent clinical data demonstrating improved survival in children presenting to higher‐pediatric‐volume EDs and academic medical centers …”
Section: Discussioncontrasting
confidence: 95%
“…In the United States, ED care is provided to these children across a spectrum of over 5,000 hospitals . Survival rates for nontraumatic p‐OHCA are higher in EDs that care for children only compared to EDs that care for a mix of adults and children (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.7–2.8) . Improved survival has also been noted when children are cared for in EDs classified as teaching hospitals (OR = 0.57, 95% CI = 0.50–0.66) or trauma centers (OR = 0.76, 95% CI = 067–0.86) .…”
mentioning
confidence: 99%
“…Emergency department visits were classified as occurring at either a pediatric or general ED. A pediatric ED was defined as having more than 75% of its visits made by patients under 18 years of age …”
Section: Methodsmentioning
confidence: 99%
“…In terms of patient outcomes, mortality is the ultimate outcome that differs by type of ED. Children with atraumatic out‐of‐hospital cardiac arrest have higher survival in pediatric EDs than general EDs (33.8% vs. 18.9%, p < 0.001) with an adjusted OR of survival in pediatric ED compared to general EDs of 2.2 (95% CI = 1.7–2.8) . Other studies have shown similar findings, with halved mortality rates in very high pediatric volume EDs (≥50,000 annual pediatric visits per year) compared with low‐pediatric‐volume EDs …”
mentioning
confidence: 63%